Coronary 18F-sodium fluoride PET detects high-risk plaque features on optical coherence tomography and CT-angiography in patients with acute coronary syndrome. (February 2021) - Majeed, Kamran; Bellinge, Jamie W.; Butcher, Steele C.; Alcock, Richard; Spiro, Jon; Playford, David; Hillis, Graham S.; Newby, David E.; Mori, Trevor A.; Francis, Roslyn; Schultz, Carl J.
Abstract: Background and aims: 18 F-Sodium Fluoride Positron Emission Tomography ( 18 F–NaF PET) non-invasively detects micro-calcification activity, the earliest stage of atherosclerotic arterial calcification. We studied the association between coronary 18 F–NaF uptake and high-risk plaque features on intra-coronary optical coherence tomography (OCT) and CT-angiography (CTCA) and the potential application to patient-level risk stratification. Methods: Sixty-two prospectively recruited patients with acute coronary syndrome (ACS) underwent multi-vessel OCT, 18 F–NaF PET and CTCA. The maximum tissue to background ratio (TBRmax = standardised uptake value (SUV)max/SUVbloodpool) was measured in each coronary segment on 18 F–NaF PET scans. High-risk plaque features on OCT and CTCA were compared in matched coronary segments. The number of patients testing positive (>2SD above the normal range) for micro-calcification activity was determined. Results: In 62 patients (age, mean ± standard deviation (SD) = 61 ± 9 years, 85% male) the coronary segments with elevated 18 F–NaF uptake had higher lipid arc (LA) (median [25th-75th centile]: 74° [35°–117°] versus 48° [15°–83°], p= 0.021), higher prevalence of macrophages [n(%): 37 (62%) versus 89 (39%), p= 0.008] and lower plaque free wall (PFW) (50° [7°–110°] versus 94° [34°–180°], p= 0.027) on OCT, and a higher total plaque burden ( p= 0.011) and higher dense calcified plaque burden ( p= 0.001) on CTCA, when compared with 18 F–NaF negative segments. Patients grouped by increasing number of coronary lesions positive for microcalcification activity (0, 1, ≥2) showed decreasing plaque free wall, increasing calcification and increasing macrophages on OCT (respectively p= 0.008, p  < 0.001 and p= 0.028). Conclusions: 18 F–NaF uptake is associated with high-risk plaque features on OCT and CTCA in a per-segment and per-patient analysis in subjects hospitalized for ACS. Graphical abstract: Central Illustration: Representative examples of 18F-NaF PET tracer uptake in 3 subjects. On co-registered PET and CT-angiography, the arrows demonstrate the proximal left anterior descending artery (A, C, D). Subject 1 shows 18F-NaF positive uptake in the LAD (A) with OCT plaque features (B) from the same segment. In (B) the OCT cross-sectional image demonstrates lipid (indicated by a star), calcium (indicated by a triangle) and macrophages (left arrow). Subjects 2 and 3 respectively show 18F-NaF PET-positive and negative coronary segments of the proximal left anterior descending artery (C&D). Image 1 Highlights: Coronary 18 F-NaF uptake detects plaque with high-risk features on optical coherence tomography. Coronary 18 F-NaF uptake identifies plaque with higher total plaque burden and calcification on CT-coronary angiography. Patients with an increasing number of 18 F-NaF positive coronary lesions have an increasing high-risk plaque phenotype.